STATE-CHURCH LAW IN THE KINGDOM OF THE SERBS, CROATS, AND SLOVENES UNTIL 1930: LEGISLATIVE ACTS ON RECOGNIZED RELIGIONS - Vasiljević, Aleksandar (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The plurality of state-church relations points to the need for a typology of possible relations within which it is possible to recognize the specificities of our time and space. In this paper, the reflections are directed towards a legal-historical approach to state-religious regulation in the First Yugoslavia. The “new state” established a special policy of state-religious law. By eliminating the concept of a “state church” and changing the model of state-church relations, the effect of resolving complex issues of the legal status and activities of churches and religious communities was achieved. Systematic legislation ensured consistent treatment of traditional churches and religious communities, which made the complex mutual relations of distant communities follow the process of integration and mutual coalition. State-religious law in Yugoslavia and the concept of state and national unity, promotes a flexible relationship between different confessions and balance in communication with other religious communities.